Smart materials technologies III 3rd International Conference on Smart Materials Technologies (3rd ICSMT 2018) : selected peer reviewed papers from the 3rd International Conference on Smart Materials Technologies (ICSMT 2018), June 21-23, 2018, Moscow, Russia - Polyakova, Marina (Key engineering materials, 2018)
The 3rd International Conference on Smart Materials Technologies (ICSMT 2018) was held in Moscow, Russia during June 21-23, 2018. The objective of ICSMT 2018 was to bring together researchers, scientists, engineers and scholar students in the field of materials science and materials processing technologies to exchange and share their experiences, new ideas, and research results, and discusses the practical challenges encountered and the solutions adopted.